2022
DOI: 10.1186/s12903-022-02195-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of biofilm removal by combination of water jet and cold plasma: an in-vitro study

Abstract: Background Peri-implantitis therapy is a major problem in implantology. Because of challenging rough implant surface and implant geometry, microorganisms can hide and survive in implant microstructures and impede debridement. We developed a new water jet (WJ) device and a new cold atmospheric pressure plasma (CAP) device to overcome these problems and investigated aspects of efficacy in vitro and safety with the aim to create the prerequisites for a clinical pilot study with these medical devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…The CAP discharge properties were comparable to the formerly used plasma source kINPen 09 [ 32 ]. The ability of CAP to enhance the wettability on titanium implant surfaces was previously presented [ 58 ], which supports human cell attachment and possibly subsequent healing processes [ 46 , 52 , 59 , 60 , 61 ]. For implant treatment, the CAP device was hand-held and moved in angles between 20° and 90° horizontally and vertically along the implant (fixed in the microtiter plate model, see above) for 120 s ( Figure 1 c).…”
Section: Methodsmentioning
confidence: 82%
“…The CAP discharge properties were comparable to the formerly used plasma source kINPen 09 [ 32 ]. The ability of CAP to enhance the wettability on titanium implant surfaces was previously presented [ 58 ], which supports human cell attachment and possibly subsequent healing processes [ 46 , 52 , 59 , 60 , 61 ]. For implant treatment, the CAP device was hand-held and moved in angles between 20° and 90° horizontally and vertically along the implant (fixed in the microtiter plate model, see above) for 120 s ( Figure 1 c).…”
Section: Methodsmentioning
confidence: 82%
“…This is in line with other findings [ 22 ]. The improvement in initial attachment demonstrated in this study provides the opportunity for use of cold atmospheric plasmas in implantology, both in primary implant placement and in the regeneration of lost attachment due to peri-implantitis [ 33 , 34 ]. Additionally, cold atmospheric plasmas can be used for the disintegration of biofilms on implant surfaces [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no evidencebased guidelines or protocols for the nonsurgical and surgical therapy of peri-implantitis. [74,75] The microbiota associated with peri-implantitis is dominated by wellknown periodontal pathogens such as P. gingivalis, T. forsythia, and Treponema denticola, suggesting that similar antimicrobial strategies used in periodontal disease, such as manual or mechanical biofilm removal, may be applied. [67,76] However, the complex geometries of the implant surface and peri-implant defects create an additional challenge for successful instrumentation and decontamination.…”
Section: Peri-implant Diseasementioning
confidence: 99%
“…It also has the potential to perform biocompatible surface modifications, influencing cell adhesion, or enabling the addition of antibacterial coatings and promoting wound healing properties. [75,77] Studies have shown that using cold plasma alone or in combination with mechanical pretreatment can effectively decontaminate surfaces under specific conditions. [9] For instance, Carreiro et al studied the effect of LTP on P. gingivalis biofilm and a reconstituted human gingival epithelium.…”
Section: Peri-implant Diseasementioning
confidence: 99%
See 1 more Smart Citation